Correction: Assessment of the transmission blocking activity of antimalarial compounds by membrane feeding assays using natural Plasmodium falciparum gametocyte isolates from West-Africa. - Noëlie B Henry; Issiaka Soulama; Samuel S Sermé; Judith M Bolscher; Tonnie T G Huijs; Aboubacar S Coulibaly; Salif Sombié; Nicolas Ouédraogo; Amidou Diarra; Soumanaba Zongo; Wamdaogo M Guelbéogo; Issa Nébié; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0284751.].